What are Program Officer’s Responsibilities and Competencies? An Exploratory Research on Human Resource Development Policy for Effective Grantmaking - Shimizu Junko; Nakajima Takako; Sugano Taku (Nonprofit Policy Forum, 2025)
The development of human resources is a significant issue in the global nonprofit context, and Japan is no exception with its relatively small philanthropic sector. In such countries, the government can be regarded as a potential resource provider. Nevertheless, thus far the Japanese government’s support for the nonprofit sector has been limited to taxation and corporate law. However, the act on utilization of funds related to dormant deposits to promote public interest activities by the private sector became the first policy measure related to nonprofit human resource development, especially focusing on the program officer (PO)’s roles via nonprofit sectorial capacity-building. In order to maximize this political opportunity, it is indispensable to fundamentally address the questions identifying what competencies and responsibilities are expected from POs and what kind of individuals are engaged. This research conducted exploratory research to elucidate this in Japan, gaining insights for advancing future human resource development policies. The results illustrated that POs were well-educated and had experience working in various sectors. Moreover, years of experience had a statistically significant relationship with their roles and the competencies they considered important. Furthermore, the results highlighted the limited training opportunities for POs and suggested that sector-related policies influence the environment in which POs develop and operate. This study indicates the importance of developing human resources in the nonprofit sector by collaborating beyond sectors and sheds light on the opportunities to utilize government policy measures for nonprofit capacity-building.